Attitudes towards human papillomavirus vaccination: a qualitative study of vaccinated and unvaccinated girls aged 17–18 years. Issue 1 (10th January 2011) - Williams, Kate; Forster, Alice; Marlow, Laura; Waller, Jo
Abstract : Background and methodology: This study explored knowledge about human papillomavirus (HPV) and attitudes towards HPV vaccination among girls who were part of the 'catch-up' vaccination programme. Interviews were carried out between March and May 2009 with girls (aged 17–18 years) who had received HPV vaccine ( n =5) and girls who had opted not to receive HPV vaccine ( n =5). Interviews lasted approximately 25 minutes, were recorded and transcribed verbatim. The data were analysed qualitatively using framework analysis. Results: Most girls were aware that HPV is sexually transmitted, but beyond this had limited understanding of HPV and HPV vaccination, and expressed a desire for further information. Girls were uncertain about the need for the vaccine both in terms of perceived risk (e.g. because they were not sexually active) and because of its novelty. Some had concerns about the efficacy and safety of the vaccine, while others were mistrusting of the information provided. Being embarrassed about discussing the vaccine with parents and practical barriers to vaccination were also discussed. Discussion and conclusions: Understanding of HPV was poor, despite participants having been offered the vaccine. School-based interventions might be a useful supplement to leaflets, and should focus on improving knowledge of HPV and awareness of the purpose of HPV vaccination.